Antisense oligonucleotide reverses topotecan-resistant ovarian cancer cells - Jia, Ping; Wu, Shao-Bo; Xu, Qian; Wu, Ming-Fu; Gao, Qing-Lei; Liao, Guo-Ning; Lu, Yun-Ping; Ma, Ding (Ai zheng = Aizheng = Chinese journal of cancer, 2003)
Breast cancer resistance protein (BCRP) was overexpressed in topotecan (TPT)-selected human ovarian cancer cell line A2780/TPT, strongly suggesting BCRP to be responsible for the drug-resistance of ovarian cancer. The current study was designed to investigate the reversal effect of BCRP antisense oligonucleotide (ASODN) on topotecan- resistant A2780/TPT cells. The antisense-phosphorothioate oligonucleotide including the translation initiation site of BCRP mRNA was artificially synthesized, and the sense oligonucleotide (SODN) corresponding to the ASODN was also synthesized as control. Lipofect-2000 (LF) was used for the transfer of either ASODN or SODN into A2780/TPT cells. The changes of BCRP mRNA expression, intracellular fluorescence intensity of rhodamine and resistance index to topotecan of in vitro transfected A2780/TPT cells were detected respectively by reverse transcription-polymerase chain reaction (RT-PCR),flow cytometry (FCM),and methyl thiazolyl tetrazolium (MTT) assay. The transfer of ASODN/LF i